Territorial and ethnic distribution of mutant alleles of BCKDHB and DBT genes of Azerbaijani patients - Huseynova, L.S.; Hagverdiyeva, R.R.; Hashimova, A.R.; Eyvazova, Sh.R.; Jafarova, A.M. (International Journal of Innovative Research and Scientific Studies, 2025)
Maple Syrup Urine Disease (MSUD) is an inherited metabolic disorder caused by mutations in the genes BCKDHA, BCKDHB, DLD, and DBT, which are involved in the breakdown of branched-chain amino acids (BCAAs). The research aimed to characterize these mutations among MSUD patients from different regions and ethnic groups within Azerbaijan. Polymerase Chain Reaction (PCR) was used to amplify the genes BCKDHA, BCKDHB, DLD, and DBT. Blood samples were collected from 940 patients diagnosed with MSUD, and exome sequencing along with Sanger sequencing were employed for detailed analysis. The study involved patients from various regions of Azerbaijan, including Sheki-Zagatala, Guba-Khachmaz, Lankaran-Astara, and Baku. These areas have diverse ethnic groups, with the study specifically noting patients from the Azerbaijani Turk and Lezgi ethnic groups in the Guba-Khachmaz zone. DBT gene: The 1199A>G mutation was found in a homozygous form in one patient. BCKDHB gene: The 508C>T mutation was found in a homozygous form in a second patient. BCKDHB gene: In a third patient, the 972C>T (exon 9) and 1221A>G (exon 10) mutations were found in a compound heterozygous form. The 508C>T mutation (BCKDHB gene) caused a Lys-Gly change at position 332 in the corresponding polypeptide. The 972C>T and 1221A>G mutations in the BCKDHB gene caused changes at positions 673 and 947, resulting in Arg673Ser and Phe947Gly substitutions. The 1199A>G mutation in the DBT gene caused a Lys508Gln change at the corresponding position. Using Swiss modeling software, the protein structures were analyzed. The 508(C>T) mutation affected the protein helix structure. The Arg673Ser and Phe947Gly mutations were observed in the protein coils. The Lys907Gly mutation resulted in an extension of the β-sheet structure. The study highlights the importance of genetic testing for MSUD, especially in regions with diverse ethnic populations like Azerbaijan. The novel mutations discovered provide essential information for genetic counseling, diagnosis, and treatment of MSUD. Furthermore, the territorial and ethnic distribution of these mutations offers valuable insights into molecular diagnostics and understanding the genetic diversity of the disease in Azerbaijani populations. The findings underline the critical role of identifying genetic mutations in MSUD, facilitating early diagnosis and personalized treatments. Additionally, the study demonstrates the significance of regional and ethnic variations in genetic diseases, which can inform better-targeted healthcare strategies for diverse populations.